Fundamentals of corporate finance / Richard A. Brealey, London Business School, Stewart C. Myers, Sloan School of Management, Massachusetts Institute of Technology, Alan J. Marcus, Carroll School of Management, Boston College. - Brealey, Richard A.,author.
Includes bibliographical references and index.